Analysis of nutritional supplements and their efficacy in extraction socket healing in patients undergoing orthodontic extraction of maxillary premolar – A split-mouth Study - BULDEO , Janhavi; VISHNAVI , Rozina; MADHU , Priyanka Paul; RECHE , Amit; WADHER , Bhinika; MIGLANI , Abhinn; DESHPANDE, Mihika (International Arab Journal of Dentistry (IAJD), 2024)
Introduction: Nutritional supplements have been known to play an effective role in wound healing. Lack of nutrition has been linked to a decline in wound tensile strength and increased infection rates. The present study aims to compare and evaluate the efficacy of nutritional supplements on the healing of the socket in patients undergoing bilateral maxillary first premolar extraction. Methods: This prospective split-mouth trial includes twenty patients undergoing orthodontic treatment and requiring bilateral maxillary first premolars extraction. They were split into two groups: ‘Group 14’ received only analgesics, while ‘Group 24’ received analgesics and additional supplements of multivitamins and minerals. Both the groups underwent extractions at the gap of one month in which ‘14’ was extracted prior to ‘24’ and socket dimensions, Buccolingual width (B), Mesiodistal width (M), and Depth (D) were measured on the day of extraction, day seven and day twenty-one to assess healing. Results: In this study, 20 patients were split into ‘Group 14’ (no supplements) and ‘Group 24’ (with supplements). The patients, 10 males and 10 females had an average age of 18.20 ± 3.23 years. ‘Group 24’ had a slight reduction in M width on day seven and a slight reduction in B width on day twenty-one when compared to ‘Group 14’. However, no values were statistically significant. Conclusions: The study shows that nutritional supplements led to slight socket healing improvement, but this wasn’t statistically significant. It recommends nutrient-rich diets for healing, alongside balanced nutrition, oral hygiene, and advice post-operative instructions.